Impact and durability properties of alccofine-based hybrid fibre-reinforced self-compacting concrete - S.S. Vivek; B. Karthikeyan; Alireza Bahrami; Senthil Kumaran Selvaraj; R. Rajasakthivel; Marc Azab (Case Studies in Construction Materials, 2023)
Many research works have already been made and are still in progress on metallic fibres, as their incorporation reduces the brittleness of the concrete and improves its resistance to the impact and crack propagation. But the use of such non-metallic fibres may induce corrosion which is a major problem to be addressed from the durability aspect. To overcome this problem, in the present research work, a non-metallic hybrid fibre combination was investigated with synthetic fibres like polypropylene and abaca fibres. Also, rather than using conventional cementitious materials such as silica fume, fly ash, and ground granulated blast furnace slag, a new generation of ultra-fine material namely alccofine was used as a partial replacement for the cement by 15%. Abaca fibre was utilised in a constant addition of 0.5% and blended with polypropylene fibre in a range varying from 0% to 2% with an increment of 0.5%. The fresh properties of self-compacting concrete (SCC) in mono and hybrid fibres combinations were assessed through slump flow, J-ring, and V-funnel tests. Water absorption and sorptivity tests were conducted to ensure the durability of the prepared mix. Further, impact tests were carried out on the prepared cylinder specimens to check the capability of the mix with the non-metallic hybrid combination. The main objective here was to check whether a high-strength durable SCC could be achieved using non-metallic fibres and natural fibres. From the obtained experimental results, it was observed that 15% alccofine as a partial substitute to the cement with the addition of 0.5% of abaca fibre and 2% of polypropylene fibre to SCC performed better than the control SCC.